A comparative study of heavy metals removal using agricultural waste biosorbents. (September 2021) - Tokay, Begum; Akpınar, Işıl
Abstract: The adsorption capabilities of rice husk, coconut coir and moringa seeds were evaluated for the first time under the same experimental conditions for the removal of copper (Cu), nickel (Ni) and zinc (Zn from underground water. The effects of adsorbent dosage, pH and contact time were studied. Copper and nickel were removed up to 99%, using rice husk, coconut coir and moringa seeds. Zinc concentrations can only be reduced to up to 70% using rice husk. However, removal was reached 99% when coconut coir and moringa seeds were used. Moring seeds showed the highest adsorption capacities (Zn = 42.3 mg g −1, Cu = 23.3 mg g −1, Ni = 16.1 mg g −1 ) among the biosorbents tested. Nickel was the least adsorbed heavy metal for all biosorbents studied. Moringa seeds leached sulfur at acidic pH values (< 4). Models showed that adsorption using these biosorbents follows Langmuir isotherm and Pseudo-second order kinetic. Graphical abstract: Unlabelled Image Highlights: Heavy metals were removed up to 99% with rice husk, moringa seeds and coconut coir. The highest adsorption capacities were observed using moringa seeds. Adsorption isotherms and kinetics followed Langmuir and pseudo-second order models. Sulfur leaching was recorded using moringa seeds at acidic pH for the first time.